Differential gene expression in the nucleus accumbens with ethanol self-administration in inbred alcohol-preferring rats - Rodd, Zachary A. (Pharmacol Biochem Behav, 2008)
The current study examined the effects of operant ethanol (EtOH) self-administration on gene expression in the nucleus accumbens (ACB) and amygdala (AMYG) of inbred alcohol-preferring (iP) rats. Rats self-trained on a standard two-lever operant paradigm to administer either water-water, EtOH (15% v/v)-water, or saccharin (SAC; 0.0125% g/v)-water. Animals were killed 24 hr after the last operant session, and the ACB and AMYG dissected; RNA was extracted and purified for microarray analysis. For the ACB, there were 513 significant differences at the p < 0.01 level in named genes: 55 between SAC and water; 215 between EtOH and water, and 243 between EtOH and SAC. In the case of the AMYG (p < 0.01), there were 48 between SAC and water, 23 between EtOH and water, and 63 between EtOH and SAC group. Gene Ontology (GO) analysis indicated that differences in the ACB between the EtOH and SAC groups could be grouped into 15 significant (p < 0.05) categories, which included major categories such as synaptic transmission, cell and ion homeostasis, and neurogenesis, whereas differences between the EtOH and water groups had only 4 categories, which also included homeostasis and synaptic transmission. Several genes were in common between the EtOH and both the SAC and water groups in the synaptic transmission (e.g., Cav2, Nrxn, Gabrb2, Gad1, Homer1) and homeostasis (S100b, Prkca, Ftl1) categories. Overall, the results suggest that changes in gene expression in the ACB of iP rats are associated with the reinforcing effects of EtOH.